2020
DOI: 10.1080/07448481.2020.1820511
|View full text |Cite
|
Sign up to set email alerts
|

College students’ comfort with and intention to use self-collection services for STI testing

Abstract: Objective: Sexually transmitted infections (STIs) are at unprecedented levels; yet most college students have never been tested. Offering asymptomatic individuals the option to collect their own samples for STI testing is an effective strategy to increase testing coverage. This study explores students' perceptions of self-collection services. Participants: Four hundred and thirty-four (434) students from a large public university completed an online survey in February 2018. Methods: The cross-sectional survey … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
21
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(23 citation statements)
references
References 22 publications
0
21
0
2
Order By: Relevance
“…Although university communities are not formally considered as a key population for HIV infection, this population tends to engage in behaviors that put them at risk of STIs such as alcohol use, illicit drugs use, permissive attitudes toward casual sex, history of STI diagnosis, poor STI knowledge, and low STI and HIV testing rates. 16–22 The importance of identifying university population as a STI at risk group was illustrated by a 2003 outbreak of HIV infection in North Carolina, USA. 23…”
Section: Discussionmentioning
confidence: 99%
“…Although university communities are not formally considered as a key population for HIV infection, this population tends to engage in behaviors that put them at risk of STIs such as alcohol use, illicit drugs use, permissive attitudes toward casual sex, history of STI diagnosis, poor STI knowledge, and low STI and HIV testing rates. 16–22 The importance of identifying university population as a STI at risk group was illustrated by a 2003 outbreak of HIV infection in North Carolina, USA. 23…”
Section: Discussionmentioning
confidence: 99%
“…Studies have found that fear of getting hurt during sampling or not collecting the sample correctly, as well as concerns about cost, accuracy, and confidentiality, can reduce willingness to self-collect. 25,26,33 However, one study found that acceptability of self-collection increases over time, suggesting increased acceptability with additional information and education around self-collection. 18 It is also important to assess attitudes and acceptance of self-care methods among those who would not otherwise seek care, to see if these methods would facilitate the testing and treatment of STIs that would otherwise go undetected.…”
Section: Discussionmentioning
confidence: 99%
“…Rates of sexually transmitted infections (STIs) are highest among those in the traditional undergraduate students’ age range [ 19 ]. US samples of undergraduate students highlight inconsistent condom or other protective barrier use during sex [ 17 ], along with low rates of testing for STIs [ 20 ]. US undergraduates, particularly females, report very high rates of dating and intimate partner violence [ 21 ].…”
Section: Introductionmentioning
confidence: 99%